MANAGING HUMAN RESOURCE THROUGH GREEN POLICY: WAYS OUT AND ITS IMPLICATION - Hossen, Md. Miraj; Begum, Mareum; Sultana, Fatema (TRIKONOMIKA, 2018)
This paper attempts to highlight the green policy and its practices for managing the human resource in the organizations and also seeks to ways out some techniques to make green HR policy useful for the organizational practices. In this study, the authors used secondary data through an extensive literature survey form different sources. The significant findings are that all over the world, organizations are trying to practice green management or implementation of green policy for their daily activities as well as to ensure the health and well-being of their human resources. Though the green system is beneficial for both the organizations as well as employees but it costs a lot in the initial stage to meet up the preliminary fixed costs, train the people and to make people ready to work as per green policies. Gathering experiences from different research in advanced countries the authors try to conclude the study by mentioning some ways- how to manage HR through green policy or green human resource management (HRM) techniques.